Corporate Social Responsibility: Analisis Variabel Anteseden dan Konsekuensi - Masmira Kurniawati; Sri Hartini; Lilik Rudianto (Forum Manajemen Indonesia (FMI), 2014)
This study is exploratory in nature and tries to explain buying consumer behavior of environmental friendly product. Specifically, this study focuses on the antecedents and consequences of corporate social responsibility (CSR) strategy and its impact on marketing outcome using qualitative method. Information on identification of consumer’s buying decision process of green marketing products, types of CSR, and marketing outcomes based on customer’s perspectives are gathered through in-depth interview. Nine propositions in relation to the antecedents and consequences of corporate social responsibility strategy from customer perspectives proposed from this study are: (1) consumer perception of CSR activity objectives influences consumer evaluation on CSR activity; (2) consumer evaluation on CSR activity influences consumer buying decision; (3) CSR activity influences customer value; (4) CSR activity creates consumer skepticism toward company; (5) product-related CSR activity which directly impact on consumer will increase consumer attitude toward product; (6) CSR activity influences consumer perception on company’s and product’s image and increase company as well as brand reputation; (7) consumer judgment on CSR activity influences consumer loyalty; (8) consumer characteristics strengthen the impact of CSR toward consumer buying decision; (9) consumer culture of collectivism influences their attitude toward CSR activity and buying decision of environmental friendly product. Keywords: corporate social responsibility, green marketing, marketing outcome, qualitative method